FRI0661 Capillaroscopy in patients with silica exposure. a case control study. (15th June 2017) - Freire, M; Perez-Gonzalez, A; Arnalich, V; Boveda-Ruiz, D; Salgado, A; Blanco-Perez, JJ
Abstract : Background: Exposure to silica dust has been associated with different autoimmune diseases and immunological abnormalities in which microvascular involvement is very common, as systemic sclerosis, systemic lupus erythematosus, rheumatoid arthritis or dermatomyositis. Objectives: To show capillaroscopic findings in patients exposed and not exposed to silica and to analyze the differences between both groups. Methods: A case control design was made. Cases (Si+) were subjects exposed to silica (with and without silicosis). Controls (Si-) were healthy subjects not exposed to silica. Capillaroscopy was made with both Zuzi® Optical stereo microscope with Optikam® camera adapted and with USB Digital Microscope Video epiluminiscence Dino-Lite ® in each patient. The capillaroscopic alterations were evaluated according to a semiquantitative method. Background data on CVRF and variables related to capillaroscopy were collected. A comparative study was done. Results: Capillaroscopy was performed on 61 Si+ and 12 Si- subjects. Mean age of Si+ was 52.6 years (SD: 7.3) and 54 years (SD: 6.6) in Si-. There were no significant differences in CVRF: hypertension (13.1% Si+ and 8.3% Si-), diabetes mellitus (3.3% Si+ and 8.3% Si-) and tobacco exposure (18.0% Si+ and 25.0% Si-). It was observed capillary dilation in 24 (33.9%) Si+ and only in 3 (25.0%) Si-. The dilation score was mild in all Si- while in Si+ was mild in 41.7%, moderate in 37.5% and extreme in 12.5%. 42.7% of Si + had a degree of tortuosity higher than 33% (score 2) whereas in all Si- the degree of tortuosity was <33% (score 1). Capillaroscopic general pattern showed differences between both groups: it was normal in 24 (42.1%) Si+ and 9 (75%) Si-; slightly irregular in 30 (52.6%) Si+ and 3 (25%) Si- and unstructured in 3 Si+ (5.3%) and in none Si-. Conclusions: The current study shows significant differences between the capillaroscopy of subjects exposed and not exposed to silica, with a trend in more frequency and severity of capillary dilatation, greater frequency of tortuosity in a severe degree and more frequent irregular capillaroscopic pattern in the exposed patients. References: Blanc PD, Järvholm B, Torén K. Prospective risk of rheumatologic disease associated with occupational exposure in a cohort of male construction workers. Am J Med 2015;128(10):1094–101. Disclosure of Interest: None declared